2019
DOI: 10.1080/10717544.2018.1556361
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of erythropoietin rescues the photoreceptors in degenerative retina: a noninvasive method to deliver drugs to the eye

Abstract: Inherited retinopathies typically lead to photoreceptor loss and severe visual impairments in the subjects. Intranasal administration is an efficient approach to deliver therapeutic agents to the targeted tissue. The present study is designed to deliver the erythropoietin (EPO) into the N-methyl-N-nitrosourea (MNU) induced mice, a pharmacological retinopathy model via intranasal or intravenous route. The mice were then subjected to bioavailability assay and therapeutic effects evaluation. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…174 Furthermore, a series of studies in the 1990s identified sudden retinal manifestations associated with intranasal abuse of cocaine and methamphetamine. 175,176 This marked the beginning of exploration into the effects of IN applications on the eye like the IN administration of the secretome of amnion-derived multipotent progenitor cells, rich in growth factors and anti-inflammatory cytokines, found to attenuate visual dysfunction and prevent retinal ganglion cell (RGC) loss 177 or IN administration of erythropoietin to rescue photoreceptors in the degenerative retina, highlighting the benefits of this noninvasive and efficient approach 172 It can be expected that further studies will evaluate the capacity of various intranasal nanoformulations, including naı ¨ve and drug-loaded EVs, to exert beneficial effects on the retina. Improving the efficiency of the IN administration of EVs will hopefully benefit from the experience gained with other drugs or NPs.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…174 Furthermore, a series of studies in the 1990s identified sudden retinal manifestations associated with intranasal abuse of cocaine and methamphetamine. 175,176 This marked the beginning of exploration into the effects of IN applications on the eye like the IN administration of the secretome of amnion-derived multipotent progenitor cells, rich in growth factors and anti-inflammatory cytokines, found to attenuate visual dysfunction and prevent retinal ganglion cell (RGC) loss 177 or IN administration of erythropoietin to rescue photoreceptors in the degenerative retina, highlighting the benefits of this noninvasive and efficient approach 172 It can be expected that further studies will evaluate the capacity of various intranasal nanoformulations, including naı ¨ve and drug-loaded EVs, to exert beneficial effects on the retina. Improving the efficiency of the IN administration of EVs will hopefully benefit from the experience gained with other drugs or NPs.…”
Section: Perspectivesmentioning
confidence: 99%
“…Similar considerations apply to crossing the BRB, where uncertainties surrounding the technical capacity to develop nanoformulations that can cross the BRB have stimulated interest in using the IN route as a means of delivering drugs to the retina. 172 Retrospectively, these attempts can be traced back to the progressive understanding of the connection between the nasal cavity and the retina with a link found between the IN administration of prednisolone and the occurrence of retinal vein thrombosis 173 or the observation that IN administration of corticosteroids induced retinal and choroidal microvascular embolism. 174 Furthermore, a series of studies in the 1990s identified sudden retinal manifestations associated with intranasal abuse of cocaine and methamphetamine.…”
Section: Perspectivesmentioning
confidence: 99%
“…7e ) 90 . Compared with intravenous delivery, intranasal delivery allows the regulation of retinal degenerative cell apoptosis and inhibition of oxidation for more effective protection and erythropoiesis, which also reduces ocular tissue damage 91 . Moreover, drug innovations have greatly improved the therapeutic efficacy.…”
Section: Micro/nanodevices For Treatmentmentioning
confidence: 99%
“…Interestingly, erythropoietin may be administered intranasally and appears to protect photoreceptors when delivered by that route in a pharmacologic model of retinal degeneration. 34 Finally, analysis of the potential neuroprotectant endothelin-2 suggests unexpected complexity in local and systemic effects of these potential agents. 35 Endothelin-2 is a vasoactive peptide initially purified from vascular endothelium.…”
Section: Neuroprotectants and Immune Modulatorsmentioning
confidence: 99%
“…(It should be noted this is one of the first studies to employ MEA in the study of the rescue of retinal degeneration; this technique may offer more sensitivity and information than classic ERG.) Interestingly, erythropoietin may be administered intranasally and appears to protect photoreceptors when delivered by that route in a pharmacologic model of retinal degeneration 34…”
Section: Neuroprotectants and Immune Modulatorsmentioning
confidence: 99%